ANALISIS IMPLEMENTASI KEBIJAKAN KETERTIBAN TERMINAL PENUMPANG TIPE A W.A. GARA PALANGKA RAYA: ANALYSIS OF POLICY IMPLEMENTATION PASSENGER TERMINAL TYPE A W.A. GARA PALANGKA RAYA - Sungkowo, Senen Suko; Nurhasanah, Nurhasanah; Bernardianto, Raden (Pencerah Publik, 2022)
Order Policy Implementation Passenger Terminal. The purpose of this study was to analyze the implementation of the policy in order Palangkaraya City passenger terminal. Design used in this study is a qualitative method. This method of choice for researchers is expected to be able to uncover the reality on the field and more sensitive and adaptive to the role of various factors in the study as well as more sensitive to information that is descriptive and try to maintain the integrity of objects studied. The results indicate the implementation of policies penelitina order passenger terminal in accordance with the regulations of higher, namely Law No. 22 of 2009 on Road Traffic and Transport as well as Minister of Transportation No. 31 of 1995 on Road Transport Terminal. However, enforcement action against passenger vehicles do find problems where the structure of service unit. Passenger Terminal is currently not in accordance with the volume of work is large enough